Pachyonychia Congenita type 1 - A peerless entity - Yugandar Inakanti; Venkata Narsimha Rao Thimmasarthi; Shiva Kumar; Akshaya Nagaraj; Srilakshmi Peddireddy (Our Dermatology Online, 2015)
Pachyonychia congenita (PC) is a rare Autosomal dominant genodermatosis characterized by hyperkeratosis affecting the nails and palmoplantar areas, oral leucokeratosis, and cystic lesions. Although classically subdivided into two major variants, PC-1 (Jadassohn-Lewandowski syndrome) and PC-2 (Jackson-Lawler syndrome), according to the localization of the mutations in the KRT6A/KRT16 or KRT6B/KRT17 genes, respectively. We report a 10 year-old male patient with a history of thickened, discoloured nails, raised spiny skin lesions all over the body since birth with focal plantar keratoderma and absence of natal teeth.